2018
DOI: 10.1093/ajcn/nqy115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psyllium (Plantago ovata) fiber on LDL cholesterol and alternative lipid targets, non-HDL cholesterol and apolipoprotein B: a systematic review and meta-analysis of randomized controlled trials

Abstract: Psyllium fiber effectively improves conventional and alternative lipids markers, potentially delaying the process of atherosclerosis-associated CVD risk in those with or without hypercholesterolemia. This trial is registered at www.clinicaltrials.gov as NCT03346733.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 48 publications
0
20
0
7
Order By: Relevance
“…Additionally, although a subgroup analysis of just two studies found that psyllium intervention for a duration of greater than 10 weeks did reduce levels of total cholesterol, the primary meta‐analysis of all available data revealed no such effect. Previous meta‐analyses have demonstrated the hypocholesterolemic attributes of psyllium (Anderson et al, ; Brum, Ramsey, McRorie, Bauer, & Kopecky, ; Jovanovski et al, ), but the present review builds upon these by focusing on the efficacy of this fiber specifically in diabetic cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although a subgroup analysis of just two studies found that psyllium intervention for a duration of greater than 10 weeks did reduce levels of total cholesterol, the primary meta‐analysis of all available data revealed no such effect. Previous meta‐analyses have demonstrated the hypocholesterolemic attributes of psyllium (Anderson et al, ; Brum, Ramsey, McRorie, Bauer, & Kopecky, ; Jovanovski et al, ), but the present review builds upon these by focusing on the efficacy of this fiber specifically in diabetic cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence also suggests effectiveness of fibre on risk factors of CVD. Meta-analyses on supplementation studies using viscous soluble fibres, β-glucan, psyllium or konjac glucomannan also reported statistically significant reductions in both total and LDL-cholesterol concentrations (162)(163)(164) . Similarly, a systematic review revealed that a breakfast based on oats, barley or psyllium may lower cholesterol concentrations (165) .…”
Section: Fibrementioning
confidence: 96%
“…Two recent meta-analyses [40,41] found that daily intake of 10.2 g psyllium significantly lowered LDL-C by −0.28 mmol/L (95% CI: −0.21 to −0.31) [39] and -0.33 mmol/L (95% CI: −0.38 to −0.27) [40]; non-HDL-C was found to be lowered by −0.39 mmol/L (95% CI: −0.50 to −0.27) [41]. No clear dose-response relationship was observed, suggesting that the cholesterol-lowering benefit of psyllium intakes of ≥10 g/day will not result in bigger LDL-C lowering [41]. The recommended intake of psyllium for an optimal cholesterol-lowering and heart health benefit is 7 g/day SF from 10.2 g psyllium husk, based on the approved US FDA health claim.…”
Section: Effect Of Specific Df On Blood Lipids and Cvd Risk And Undermentioning
confidence: 99%